MENTAL HEALTH AND WORK ENVIRONMENT EFFECTS ON EMPLOYEE PERFORMANCE IN THE PUBLIC SECTOR - Makhrisyafrisal, Mohammad; Junengsih, Junengsih; Dina, Nur (Jurnal Manajemen Terapan dan Keuangan, 2026)
High administrative demands and sustained performance targets placed civil servants under continuous work pressure, making mental health and work environment critical factors in maintaining performance. This study aimed to examine the effects of mental health and work environment on employee performance at the Deputy for Small Enterprises, Ministry of Micro, Small, and Medium Enterprises. A quantitative survey method was applied using structured questionnaires distributed to 87 civil servants selected through stratified random sampling. The data were analyzed using multiple linear regression supported by validity, reliability, and classical assumption testing. The results show that mental health and work environment have positive and significant effects on employee performance, both individually and jointly. The coefficient of determination is 0.688, indicating that 68.8 percent of performance variation is explained by the two variables. These findings confirm that employee performance in the public sector is strongly influenced by psychological well-being and supportive working conditions.